Analysis and development of I-V characteristics models for nanometer size MESFETs considering fabrication parameters - Mostofa, Jobia; Ahmed, Wasi Uddin; Pia, Ummay Farha; Meghna, Tanzina Haque (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.